Polusi Udara Kendaraan Bermotor sebagai Bentuk Kejahatan Tanpa Korban - Chazizah Gusnita (UIR PRESS, 2016)
Air pollution from motor vehicles is very dangerous for human survival, especially for health. Air polluters are the people themselves. Communities become the main actors in the spread of pollution through the use of motor vehicles. Substances released from motor vehicles damage public health. Without realizing the people who become the actors at the same time become victims of air pollution. This is called a crime without a victim, the perpetrator and the victim are the same person. But on the other hand, despite the existing laws that regulate the law in environmental crimes, this crime is actually very difficult to prove. In addition to the perpetrators of pollution is also a victim, the victim of pollution is not aware of himself as the only victim who will lose health. The offender will feel his actions are legal to do. So it is necessary step integration of all parties to solve the crime without this victim.